Utilization of Soil Function Information for Assessing Soil Quality of Rice Field in the Quaternary-Tertiary Volcanic Transitional Zones in Central Java - Ajun Prayitno; Junun Sartohadi; Makruf Nurudin (Universitas Sebelas Maret, 2019)
Soil quality information of the rice field in the Quaternary-Tertiary volcanic transitional zone has not been specifically reported. Research on the assessment of soil quality widely reported only focuses on the discussion of quantitative-qualitative techniques and the use of minimum data sets without paying serious attention to the soil functions. This study aimed to assess soil quality through qualitative and quantitative methods based on the soil function information approach. The study was conducted in the quaternary-tertiary volcanic transitional zone with special cases of thick soil, high clay content, low nutrient content, high erosion, and vulnerability to landslide, which affects soil quality and farmer cultivation practice. The qualitative soil quality approach was based on the local knowledge of the farmers. The quantitative soil quality indexing was performed with the Soil Management Assessment Framework (SMAF) method to obtain sensitive indicators. The results found that the characteristics of paddy soil had high clay content and thick topsoil layers. The paddy soil is commonly called as ngrawa/mbel soil. The minimum qualitative data sets included color, plant condition, texture, ease of tillage, and drainage. Meanwhile, the minimum quantitative data sets included Na-dd, Mg-dd, texture, bulk density, porosity, and permeability. Information on soil functions obtained included the availability of nutrients, rooting media, root penetration, water storage capacity, and soil permeability. The soil function information approach can be used to assess soil quality in the quaternary-tertiary volcanic transitional zone.